1963
DOI: 10.1152/jappl.1963.18.4.687
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary diffusing capacity of athletes

Abstract: Champion swimmers have been found to have significantly higher steady-state pulmonary diffusing capacities than those measured in normal subjects of comparable age at the same exercise level. Nonactive and moderately active normal subjects, swimmers of average ability, long distance runners, and older ex-athletes were found to show no significant deviation from predicted values of DlCO, either in absolute terms or in relation to body surface area or lung midcapacity. The high DlCO in champion swimmers results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

1965
1965
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 0 publications
1
22
0
1
Order By: Relevance
“…Our findings are in agreement with others that elite swimmers exhibit elevated DL CO values, greater than predicted (Armour et al 1993;Magel and Andersen 1969;Miller et al 1989;Mostyn et al 1963;Vaccaro et al 1977) and greater than non-athletes (Andrew et al 1972;Yost et al 1981), even when corrected for body size and total lung capacity (K CO ) (Magel and Andersen 1969;Mostyn et al 1963;Yost et al 1981). It has been suggested that elite swimmers have a high DL CO , as they must be able to transfer large amounts of oxygen across the alveolar-capillary membrane when the alveolar oxygen tension (PaO 2 ) falls to low levels (Mostyn et al 1963), and that the enlarged DL CO is a consequence of an increased pulmonary capillary blood volume (Miller et al 1989).…”
Section: Respiratory Muscle Functionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our findings are in agreement with others that elite swimmers exhibit elevated DL CO values, greater than predicted (Armour et al 1993;Magel and Andersen 1969;Miller et al 1989;Mostyn et al 1963;Vaccaro et al 1977) and greater than non-athletes (Andrew et al 1972;Yost et al 1981), even when corrected for body size and total lung capacity (K CO ) (Magel and Andersen 1969;Mostyn et al 1963;Yost et al 1981). It has been suggested that elite swimmers have a high DL CO , as they must be able to transfer large amounts of oxygen across the alveolar-capillary membrane when the alveolar oxygen tension (PaO 2 ) falls to low levels (Mostyn et al 1963), and that the enlarged DL CO is a consequence of an increased pulmonary capillary blood volume (Miller et al 1989).…”
Section: Respiratory Muscle Functionsupporting
confidence: 94%
“…As well, enhanced pulmonary diffusion capacity has been reported when swimmers are compared to predicted values (Armour et al 1993;Miller et al 1989;Vaccaro et al 1980) and non-athletes (Yost et al 1981). Interestingly, Mostyn et al (Mostyn et al 1963) found that while collegiate swimmers, long distance runners and non-athletes exhibited no significant deviation from predicted values for pulmonary diffusion capacity, elite swimmers did exhibit significantly higher diffusion capacities when values are compared to predicted norms.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…W ir erklären dies dam it, daß unsere gut tra i nierten P robanden besonders schwer belastet w erden konnten. Auch ist bei S pitzensportlern die A rbeits-C O -D iffusionskapazität etw as größer gefunden w orden als beim N ichtsportler (Mostyn et al [19]); noch andere M essungen m it der CO-Mcthode zeigen allerdings d e u t lich -im G egensatz zu den eben erw ähnten daß das körperliche T raining die A rbeitsdiffusionskapazität -bei stets gleichem (^-V er brau ch -nicht w esentlich beeinflußt (Newman et al [20]). Aus A bb.2 geht hervor, daß bei G leichaltrigen die D iffusionskapazität m it dem Sauerstoffverbrauch ungefähr linear ansteigt.…”
Section: Iskussionunclassified
“…Answering these questions is beyond the scope of this paper. It should be pointed out, however, that Mostyn and his colleagues (39) found that a 7-second maximal breath-holding maneuver (similar to that required for measurement of breathholding DL) during the measurement of steadystate DL with continuous exercise caused a further increase in DL and Vc. Intra-esophageal pressures were also measured and ranged from + 12 to -20 cm H)O during the held-breath maneuver.…”
Section: Methodsmentioning
confidence: 99%